Semiotic Analysis on The Interpretation of The Dark Ages in Anime Orb: on The Movements of The Earth - Ratna Saputri, Niken; Rahmawati, Etika Laili (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Nowadays, the most popular form of animation media is anime, a form of animation media with a unique style that popularized by Japan. This research of semiotic analysis on the interpretation of the Dark Ages in anime Orb: On The Movements Of The Earth aims to find connotative and denotative signs from the anime “Orb: On the Movement of The Earth” related to the interpretation of "The Dark Ages" or the Dark Ages that occurred in Europe around the 15th century. This research using the qualitative research design with Roland Barthes’ semiotic analysis approach through the paradigm of social constructivism. As the result, the representation of the Dark Ages in anime Orb mostly revolves around the rising of science among the common ideology made by the Church. The selected scenes for this research collectively construct a mythologized narrative of the Dark Ages as a period of intellectual repression, gender inequality, and epistemological conflict. The Barthes’ semiotic approach itself helps the researcher revealing how the anime Orb used historical allegory and visual representation to align the meanings beyond the entrenched narratives of power, introducing science as both a rational and moral act of emancipation.